Preparation and Development of Transformation Systems between Ovals: - AlBarki, Ammar M.; Hamruni, Ahmed M. (Conference On Engineering Science and Technology, 2021)
Every country has its own ellipsoid (datum), for example, the used datum in Libya for production of its maps is the Libyan Geodetic Datum of 2006 (LGD2006). Recently, the use of Global Navigation Satellite Systems (GNSS) has grown rapidly. GNSS uses the World Geodetic System of 1984 (WGS1984) which does not fit the countries that use their local datums as doing so will result in errors of several metres. Because of this, it is necessary to look for new methods to accurately transform coordinates between different datums. Transformation of coordinates is not new in geodesy as it was studied by several geodesists like Bursa-Wolf method which gives approximate results as it uses the Earth as a plane. In addition, Molodensky, Helmert and others had thier methods of transforming coordinates. This paper presented developing of new method of coordinate transformation using the theory of the Russian scientist Vladimir Badchevallv. This theory gives accurate Grid and Cartesian coordinates from geodetic ones because it uses 12 variables as the more variables used, the more accurate transformation parameters we get. These new accurate parameters are then used to transform between different ellipsoids. The obtained results show that using Vladimir’s theory has improved the accuracy to the order of 0.001m which is much better than the method used by Libyan Surveying Authority, because Libyan Surveying Authority method uses only 5 variables
Keywords: Cartesian; Coordinates; Datum; Geodetic; Transformation